Regional conflict and demographic patterns on the Jesuit missions among the Guarani in the seventeenth and eighteenth centuries - Jackson, Robert H. (Robert Howard) (European expansion and indigenous response, 2019)
"In the 17th and 18th centuries Spain and Portugal contested control of the disputed Rio de la Plata borderlands. The Jesuit missions among the Guarani played an important role in regional conflict through the provision of manpower for campaigns and supplies. However, regional conflict and particularly the mobilization of the mission militia and the movement of soldiers on campaign had demographic consequences for the populations of the missions such as the spread of contagion. This study documents regional conflict in the Rio de la Plata, the militarization of the Jesuit missions, and the demographic consequences of conflict for the mission populations"--